The impact of passive ultrasonic irrigation on the bond strength of two different self-etch adhesives to human pulp chamber dentine: a laboratory investigation - Mohammed Turky; Jukka Matinlinna; Monika Lukomska-Szymanska; Venkateshbabu Nagendrababu; Paul M. H. Dummer; Ahmad Abdel Hamid Elheeny; Nermin Alsayed Mahmoud (BMC Oral Health)
Abstract Objectives To evaluate the impact of passive ultrasonic irrigation on the micro-tensile bond strength of two different self-etch adhesive systems, including a universal one-step adhesive and a two-step adhesive system, to pulp chamber dentine compared to conventional syringe irrigation. Methods Twenty-four extracted human mandibular first molar teeth were chosen according to strict criteria and mounted in epoxy resin blocks. Subsequently, the pulp chambers were exposed using an Isomet cutting machine. The specimens were numbered and assigned to four groups (6 teeth each) based on the canal irrigation method and the adhesive system used as follows: Conventional syringe irrigation in which a universal one-step self-etch adhesive system was applied (CSIU), conventional syringe irrigation in which a two-step self-etch adhesive system was used (CSIT), passive ultrasonic irrigation in which a universal one-step self-etch adhesive system was utilized (PUIU), and passive ultrasonic irrigation in which a two-step self-etch adhesive system was employed (PUIT). Following placement of the final restoration and submission to simultaneous thermo-mechanical cycling (artificial aging) equivalent to 6-month intra-oral aging, the teeth were sectioned and dentine/restoration beams were prepared. The micro-tensile bond strength was evaluated and the failure mode was defined, with a confirmatory evaluation of the dentine-resin interface using a scanning electron microscope. Statistical analysis was conducted using one-way ANOVA and Tukey’s post hoc tests to compare irrigation regimens for each adhesive technique independently, while failure modes of each adhesive system were represented as the frequency for each irrigation method. The significance level was set at 5%, with a confidence interval (CI) of 95%. Results The micro-tensile bond strength of composite resin restorations to pulp chamber dentine was reduced significantly with ultrasonic irrigation with more unfavorable failure modes compared to syringe irrigation (P < 0.0001), irrespective of the type of adhesive system used. The means of the micro-tensile strength for teeth treated with the two-step adhesive system were 26.1055 ± 4.7611 MPa and 16.0079 ± 3.7665 MPa for CSIT and PUIT, respectively. For teeth treated with the universal adhesive system, the mean for CSIU (20.1818 ± 3.8500 MPa) was significantly higher than that of PUIU (11.2090 ± 2.9928 MPa). The micro-tensile bond strength was significantly greater with the two-step adhesive system compared to the universal adhesive, regardless of the irrigation method (p < 0.05). An adhesive layer with varying thickness was noted in all groups, displaying distinct morphological features. Conclusions Within the limitations of the present laboratory investigation, ultrasonic irrigation may negatively affect the bond between composite resin restorations and pulp chamber dentine compared to conventional syringe irrigation. The two-step self-etch adhesive tended to achieve a stronger bond to pulp chamber dentine than the universal one-step self-etch adhesive. Clinical relevance While ultrasonic irrigation would be essential for effective root canal debridement and disinfection, it is imperative for clinicians to consider its potential adverse effects. This method may considerably impact the bond strength of composite resin restorations to the pulp chamber dentine, particularly when compared to conventional syringe irrigation. In root canal-treated teeth, a two-step self-etch adhesive system might be more effective in maximizing the bond strength to pulp chamber dentine than a universal adhesive system. However, these findings were concluded under the conditions of the present study and must be interpreted cautiously. Further research is recommended to validate these results and fully understand the clinical ramifications of ultrasonic irrigation on adhesive performance in different dental situations. Clinical trial number Non-applicable. Conducting the current experiment was limited to the approval of the local Research Ethics Committee at the Faculty of Dentistry, Minia University, Egypt (Committee No. 106, Registration No. 910, Date: April 30, 2024).